Magnetospheric Mass Density as Determined by ULF Wave Analysis - Takahashi, Kazue; Denton , Richard E. (Frontiers in Astronomy and Space Sciences, 2021)
The technique to estimate the mass density in the magnetosphere using the physical properties of observed MHD eigenmode oscillations is known as magnetoseismology. This technique is important in magnetospheric research given the difficulty to determine the density using particle experiments. This paper presents a review of magnetoseismic studies based on satellite observations of standing Alfven waves. The data sources for the studies include AMPTE/CCE, CRRES, GOES, Geotail, THEMIS, RBSP, and Arase. We describe data analysis and density modeling techniques, major results, and remaining issues in magnetoseismic research.